DESEMPENHO DE FORRAGEIRAS DE ESTAÇÃO QUENTE EM SISTEMAS IRRIGADOS NA REGIÃO NOROESTE DO ESTADO DO RIO GRANDE DO SUL - Maixner, Adriano R.; Sartori, César O.; Bernardi, Diego; Uhde, Leonir T.; Fernandes, Sandra B. V.; Jezewski, Tiago J. (Salão do Conhecimento, 2013)
Resumo